Design and Aerodynamic Analysis of Flapping Mechanism of Two-stage Flapping-wing Aircrafts - Sheng Dian; Zeng Zhiqiang; Wang Guanqun; Li Xinyue (Jixie chuandong)
In order to improve the flight performance of the flapping-wing aircraft, this study draws on the characteristics of the flight movement of large birds, designs a new two-stage foldable bionic flapping-wing mechanism, and establishes the kinematic and aerodynamic models of the flapping-wing mechanism. The motion performance and aerodynamic performance of the wing mechanism are analyzed. The results show that the upper flapping limit of the inner wing of the designed new folding flapping wing mechanism is 45.3°, the lower flapping limit is -5.2°, the upper flapping limit of the outer wing mechanism is 46.1°, and the lower flapping limit is -27.9°. These are consistent with the flight motion parameters of large birds; based on the strip theory and the aerodynamic model of the flapping-wing aircraft, the aerodynamic forces of the new two-stage folding flapping wing and the traditional non-folding flapping wing are calculated and compared. The average lift of the former is 4.31 times that of the latter and the two-stage folding flapping-wing flying structure has better aerodynamic characteristics.